Accelerating research on novel photovoltaic materials. (7th September 2022) - Unold, Thomas
Abstract : Massive increase of data sharing and full utilization of digitization is proposed to help accelerate novel PV material development. Abstract : The development of new materials typically takes many years or even decades. This has been particularly true for photovoltaic (PV) technologies, which require control of defects on the parts-per-million-level and consist of relatively complex device structures comprising many elements and interfaces between materials. This means that optical and electronic properties can be difficult to pin down, and also heavily depend on the details of processing. Although processing often varies from lab to lab, complete protocols are rarely reported or accessible. It is suggested that the development of novel photovoltaic materials could be greatly stimulated if information and data is more openly shared, and FAIR data management is implemented in the research community. Massive storage of research results with rich metadata in an FAIR-compliant open-access database is envisioned as a great potential for acceleration in emerging PV materials development.